Comparative survey between quantitative and qualitative paradigms (part II)‎ - Abdolhosein Emami Sigaroodi; Mahvash Salsali; HAdi Basiri (Guilan University of Medical Sciences, 2012)
As stated in the first part of article, we have stated the four major philosophical paradigms ‎which make up the basis for knowledge(epistemology), the nature and reality(ontology) and ‎the acquisition methods of knowledge(methodology). Thus, according to each paradigm, ‎approach to knowledge is determined. ‎‏ ‏ In a more general category, we have two quantitative and qualitative paradigms. Today that ‎method is called quantitative or scientific method, derived from positivism. On this basis, only ‎the experimental scientific method is valid method of research. On the other hand, qualitative ‎methods focused on natural position therefore, these studies are sometimes called naturalistic ‎study. ‎ Since paradigmatic confrontation occurs in fundamental questions of each paradigm, ‎researchers use different sources to determine two paradigms' answer to basic questions, and ‎tables are made to comprise them. Finally the importance of each was emphasized.‎